CIPP Model: Evaluation of Moral Aqidah Learning Design Program Darul Falah Islamic Boarding School, Enrekang Regency - Ushwa Dwi MasrurahAB; Sitti Mania; Nur Akbar Rashid (Universitas Muhammadiyah Enrekang, 2024)
This study aims to evaluate the moral aqidah learning design program at Darul Falah Islamic Boarding School, Enrekang Regency using the CIPP model (context, input, process and product). This evaluation aims to provide a comprehensive picture of the effectiveness of the program and identify existing strengths and weaknesses. The research method used is a qualitative approach with data collection techniques in the form of observation, interviews and documentation. While the data analysis used is descriptive analysis by reducing data, presenting data and drawing conclusions. The results of this study indicate that: (1) From the context aspect, the form of moral aqidah learning design used is the 2013 curriculum-based moral aqidah learning design which is in accordance with the vision and mission of the Darul Falah Islamic boarding school and the needs of the students determined through an agreement with teachers and leaders. Teacher qualifications are in accordance with the educational background, the pedagogic competence of some teachers is still not optimal, supporting factors of facilities and infrastructure are quite adequate. (2) From the aspect of input, school support and teacher efforts are still not optimal. (3) From the process aspect, learning is effective with interactive and participatory teaching methods, but it still needs to be improved in terms of continuous evaluation because the use of the design of learning moral aqidah is sometimes appropriate and inappropriate. (4) From the product aspect, the program used the moral aqidah learning design has succeeded in increasing the understanding and practice of the values of moral aqidah of the students, although there are some negative responses expressed by some students and educators and it also required more attention to achieve more optimal results.